Pengembangan Interface Bluetooth Low Energy (BLE) Pada IoT Middleware Untuk Mendukung Network Interoperability - Rasidy Cakra Pratama; Eko Sakti Pramukantoro; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In an earlier research developed an event-driven middleware with the ability to support the interoperability of various devices or sensors. From the results of the proposed middleware testing is able to overcome the problem of syntatic interoperability by providing gateway to communicate with IoT sensor device using MQTT and CoAP protocol, and able to communicate with other application using Websocket protocol. Reflecting on the previously offered solution to solve the interoperability problem, it is proposed another transmission line that is Bluetooth Low Energy (BLE) which will publish data to Middleware. To know the performance of BLE network transmission is tested with several parameters ie delay, bandwidth consumption, and CPU and memory usage. The test results show average CPU usage is 31% and memory usage is 5%. Delay received when using BLE transmission reaches 0.04523 seconds and when using BLE transmission along with WiFi transmission reach 0.032407248 seconds. In terms of consumption Bandwidth when using BLE transmissions reached 7786,6bits / sec and when using BLE Transmission along with WiFi Transmission doubled. From the research results show that Bluetooth Low Energy can be used to solve Interoperability problems.